Enzymatic Hydrolysis of Sweet Lupin, Chickpea, and Lentil 11S Globulins Decreases their Antigenic Activity - Elaine Sormus de Castro Pinto, Silvia [UNESP]; Neves, Valdir Augusto [UNESP]; Machado de Medeiros, Beatriz Maria [UNESP] (Amer Chemical Soc, 2009)
We investigated the effects of treatments with the enzymes pepsin and trypsin on the in vitro immunological reactivity of the major globulins found in the seeds of sweet lupin, chickpea, and lentil. Polyclonal major globulin-specific antiserum was obtained by immunization of rabbits with a solution of the 11 S globulin of each legume. The globulins were hydrolyzed with pepsin and trypsin for 1, 5, 15, and 30 min. The native globulins and their hydrolysates were analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and immunoblotting to identify the polypeptide bands with antigenic activity, and the hypoantigenicity of the hydrolysates was analyzed by enzyme-linked immunosorbent assay. Our results show that enzymatic treatment of the major storage protein (11 S globulin) of sweet lupin, chickpea, and lentil with pepsin or trypsin lead to the formation of large amounts of short peptides and free amino acids that do not allow antibody binding, resulting in a weakened immunoreactivity.
Keywords: Sweet lupin; chickpea; lentil; enzymatic hydrolysis; antigenic activity